Queen-bee evolution approach to prc-based papr reduction for ofdm systems - Laila, Binti Abg Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2011)
The thesis proposed the adoption of Queen-bee Evolution approach for Genetic Algorithm (QBEGA) concept to improve the Genetic Algorithm for generating suboptimum peak reduction carriers (PRCs) for the orthogonal frequency division multiplexing (OFDM) systems employing a large number of sub-channels as contributed by Tan (2003a). The investigations were carried out through simulation and the results and analysis obtained are discussed. The investigation concluded that the QBEGA concept performs better than the conventional GA proposed by Tan both in terms of percentage reduction and computational complexity. Irrespective of the algorithms, the findings also indicated that the performance trend improves as the initial population size increases. Nevertheless, in this regards, QBEGA concept has shown a dramatic improvement as compared to the GA.